AXIN2-Associated Adenomatous Colorectal Polyposis - Alves Martins, Bruno Augusto; Falluh Filho, Reinaldo; Almeida, Romulo Medeiros de; Sandoval, Renata Lazari (Journal of Coloproctology, 2021)
Introduction Most cases of colorectal cancer (CRC) occur sporadically; however, ∼ 3% to 6% of all CRCs are related to inherited syndromes, such as Lynch syndrome and familial adenomatous polyposis (FAP). The adenomatous polyposis coli (APC) and mutY DNA glycosylase (MUTYH) germline mutations are the main genetic causes related to colorectal polyposis. Nevertheless, in many cases mutations in these genes have not been identified. The aim of the present case report is to describe a rare case of genetic colorectal polyposis associated with the axis inhibition protein 2 (AXIN2) gene.Case Report The first colonoscopy screening of a 61-year-old male patient with no known family history of CRC revealed ∼ 50 colorectal polyps. A histological evaluation of the resected polyps showed low-grade tubular adenomas. Germline genetic testing through a multigene panel for cancer predisposition syndromes revealed a pathogenic variant in the AXIN2 gene. In addition to colorectal polyposis, the patient had mild features of ectodermal dysplasia: hypodontia, scant body hair, and onychodystrophy.Discussion The AXIN2 gene acts as a negative regulator of the Wnt/β -catenin signaling pathway, which participates in development processes and cellular homeostasis. Further studies are needed to support the surveillance recommendations for carriers of the AXIN2 pathogenic variant.
Keywords: adenomatous polyposis coli; axin protein; intestinal polyposis